Integrative modeling of FOXO-mediated autophagy in NSCLC: linking cGAS–STING signaling to IL-6 dynamics - Rani, Divya; Khandibharad, Shweta; Singh, Shailza (Frontiers in Oncology, 2025)
Lung cancer, particularly non-small cell lung cancer (NSCLC), remains the leading cause of cancer-related mortality worldwide, accounting for approximately 85% of lung cancer cases. Despite therapeutic advancements, the prognosis for advanced-stage NSCLC remains poor due to late diagnosis and high rates of therapeutic resistance. Recent studies have implicated the cyclic GMP-AMP synthase (cGAS)–stimulator of interferon genes (STING) pathway in NSCLC progression, revealing its dual role in innate immune activation and autophagy induction. Concurrently, cGAS–STING activation triggers noncanonical autophagy. We proposed a systems biology framework integrating mathematical model and network biology to elucidate how forkhead box class O (FOXOs) FOXO1 and FOXO3a serve as critical regulators linking cGAS–STING signaling with interleukin-6 (IL-6) in promoting autophagy in NSCLC. Furthermore, sequence, phylogeny, structure, domain, and protein–protein interaction studies identified crucial amino acids and their functions in regulating cGAS–STING– FOXO1 and cGAS–STING–FOXO3a interactions. Our integrative model highlights the complex interplay between immune signaling, metabolic reprogramming, and autophagic regulation in NSCLC. Further findings offer mechanistic insights into the dual role of FOXO proteins in autophagy mediated cancer progression and present potential components for the development of personalized therapeutic strategies aimed at targeting the cGAS–STING–FOXO–autophagy axis.